Estéticas da renúncia à cisgeneridade : narrativas de estilização transmasculina no Centro-Oeste brasileiro - Tchalian, Vicente (2021)
ABSTRACT: The contemporaneity and the rapid transformations that inhabit our social experiences, have opened more space for other expressions and form of experiencing human bodies, genders and sexualities in the field of hegemonic visualization. Within this context, the expressions of transmasculinities have been gaining greater expression within research, in the media, in social networks and in many other socialization spaces such as schools, the labor market, families, among others. With this in mind, bringing these experiences to be discussed within a thesis through an autoethnographic methodology can be an important contribution to the field of social, gender and masculinity studies, as well as to the field of human rights. Considering this scenario, the present doctoral thesis focuses on the processes of renouncing transmasculine and transmasculine stylization of transmen and transmasculine people in Mato Grosso. The chosen methodology was an autoethnography that has six interviews with collaborators added to the researcher's experiences, being located according to the critical perspective of contemporary gender, trans and queer studies. The questions that led this research were a) Which are the main social consequences of the process of renouncing cisnormativity, with regard to the experiences of the research collaborators? b) How are these employees building strategies to resist these social consequences? In view of the analysis of the data generated, it was possible to perceive similarities and singularities between trans and cisgender men. The factors that most tend to differ life histories are the violence committed by the family, school and work, as well as the effects of the state's control over our trans bodies. These brands modify us as much as the hormonal or surgical therapies brands and within this scenario where life expectancy does not exceed thirty-five years, it is necessary to think politics, education, health and other social relations critically and in order to centralize the issues trans, understanding that this way of thinking about life in society can prove to be quite advantageous for all people.